The Concept of Settlement in Islam - Taufiqurrahman Rahman (Universitas Darussalam Gontor, 2018)
As a complete religion, Islam not only contains the rules of worship to Allah but also the rules of human life as a khalifah on earth, including the settlement arrangement. The ways of arranging settlements based on norms and rules in Islam should be the guiding into settlement development that accommodates the need for worship, socialize with neighbours or another human, and also friendly to nature.Many settlement concepts raise a variety of problems as it is appointed to secular or atheist patterns that eliminate the God involvement in human activities and deny the position of humans as a creature created by God. The study of settlement arrangement based on the concept of Islam contains the primacy of the purpose of settlement arrangement, especially to accommodate human beings to perform the obligation to worship Allah, accommodate the human interest (work and socialize), and the principle of not destroying nature / environment in line with Islamic concept of rahmatan lilalamin.In such a situation, it is necessary to have known that the old settlements laid out in the Islamic concept established and still exist today, sustainable, and even become a big city. The methodological approach in this investigation is to analyze cases of old cities in Islamic countries in terms of the settlement development paradigm associated with the literature in Islam, including on land use, neighbouring ethics, creation of public facilities, open space, access to social services, local governance, security and safety, and socio-cultural diversity.The objective of the study of the settlement concept in Islam is to restore the original function of science as a tool of human beings in performing their duties as khalifah on earth, to worship Allah, and to protect nature from being used arbitrarily or being damaged. It is hope, Islamic settlement concept directing the realization of feasible, proper, and clean governance in Indonesia, obtain and generate into the real civilized society (Madani).